Integration of Environmental, Social and Governance (ESG) Factors in Financial Reporting: A Global Perspective - Budiasih, Yanti (Penelitian dan Pengembangan Ilmu, 2024)
The integration of Environmental, Social and Governance (ESG) considerations in financial reporting is increasingly receiving significant attention, driven by increasing investor demand and corporate social responsibility. Internal factors in an organization, such as the composition of the board of directors, financial performance, internal control system, corporate governance, and institutional environment, have a significant influence on ESG integration. This research analyzes the role of internal factors in influencing ESG practices, highlighting the importance of diverse leadership, financial stability, effective control systems, disclosure transparency, and a stable institutional environment. By paying attention to these factors, companies can improve their ESG practices, reduce risks, and make a greater contribution to sustainable economic, social, and environmental development.